THE STUDENT’S DIFFICULTIES IN LEARNING VOCABULARY USING COOPERATIVE LEARNING THROUGH PARTY GAME “UNDERCOVER” - Randi Alfi Syahr; Evie Kareviati (IKIP Siliwangi, 2022)
Enlarging and enriching student’s vocabularies have many ways, for instance by media picture to get new vocabulary, reading a story book which has a picture on it, etc. Teachers should find an easy way in teaching such as strategies, methods, techniques and interesting materials, thus that the teacher can deliver the lesson easily depending on student’s behavior and characteristic. This research is conducted to fulfill need and to find the difficulties of using game for learning purposes. The difficulties in learning vocabulary using cooperative learning through party game Undercover will be found out by interviewing and giving questionnaire that are conducted to the eighth grade students in SMPN 32 bandung, The research findings show that learning vocabulary using party games Undercover is not difficult at all. This research can be started as an evidence to convince teachers who still use rigid and serious form of teaching technique and teacher should be considering and changing their method to the one that suitable for the characteristics and behavior of their students so that the student’s learning performance can be improved and not willingly feel bored. Keywords: Vocabulary, Party Game, Cooperative Learning